http://www.rjor.ro/possibilities-of-homeopathic-treatment-of-recurrent-oral-aphthae - Sorana Maria Bucur; Stanca Ioana Bucur; Adrian Alecu; Dorin Cocoș; Anamaria Bud; Mariana Pacurar; Eugen Silviu Bud (Romanian Society of Oral Rehabilitation, 2021)
In the entire medical world and particularly in dentistry we assist to a growing tendency of patients to seek natural remedies for their ailments; this attitude stems from distrust of pharmaceutical chemicals and an attempt to avoid their side effects. The recurrent oral aphthae is a common disease of the oral mucosa, affecting, according to some authors, between 20-60% of the population depending on the socio-professional studied categories.The classic local and general treatment of the oral aphthae, especially for the chronic recurrent forms is still incomplete and unsatisfactory, with a multitude of harmful side effects. We would like to bring into the attention of our colleagues the possibilities of homeopathic treatment of this category of diseases of the oral mucosa, without harmful side effects, with concrete results in reducing the duration of lesions and the severity of symptoms.